Locally advanced nasopharyngeal follicular dendritic cell sarcoma misdiagnosed as meningioma - Yoldez Houcine; Abir Rais; Salma Kamoun; Sawssen Dhambri; Souhaeil Jebali; Maha Driss (Discover Oncology)
Abstract Follicular dendritic cell sarcoma (FDCS) is a rare malignancy, often challenging to diagnose due to its nonspecific presentation and resemblance to other neoplasms. This case highlights a locally advanced nasopharyngeal FDCS initially misdiagnosed as a meningioma, underscoring the importance of differential diagnosis in unusual tumor presentations. A 77-year-old patient presented with nasal obstruction for 3 months. Imaging studies revealed a mass in the nasopharynx prolapsing into the oropharynx, leading to an initial diagnosis of meningioma based on its radiologic appearance. Surgical resection was performed, and histopathological examination, supplemented by immunohistochmical staining, revealed features consistent with follicular dendritic cell sarcoma. The tumor was locally advanced, involving surrounding structures, which complicated the initial clinical and radiologic assessment.